Impact of privatization on employment and earnings - John S. Earle; Solomiya Shpak (IZA World of Labor, 2019)
Conventional wisdom and prevailing economic theory hold that the new owners of a privatized firm will cut jobs and wages. But this ignores the possibility that new owners will expand the firm's scale, with potentially positive effects on employment, wages, and productivity. Evidence generally shows these forces to be offsetting, usually resulting in small employment and earnings effects and sometimes in large, positive effects on productivity and scale. Foreign ownership usually has positive effects, and the effects of domestic privatization tend to be larger in countries with a more competitive business environment.
Keywords: E24; J21; J24; 330; privatization; employment; wages; earnings; productivity; output